Analysis and contrast of psoriasis disease burden trends in China and globally from 1990 to 2021 - Yu, Keyi; Cao, Cheng; An, Feilong; Xu, Aie; Wu, Xingang (Frontiers in Public Health, 2025)
ObjectiveThis study aimed to delineate the temporal tendency in the age and gender burden of psoriasis in China, spanning from 1990 to 2021, encompassing metrics such as incidence, prevalence, and disability-adjusted life years (DALYs). Furthermore, it sought to contrast these findings with the global disease burden. It also purposed to assess the impacts of age, time, and birth cohort, as well as to forecast the psoriasis burden in China for the upcoming 15 years.MethodsUtilizing open-access data from the Global Burden of Disease (GBD) database spanning 1990 to 2021, this study comprehensively examined the burden of psoriasis in China and globally. In China, a detailed analysis was conducted, emphasizing dimensions such as age, gender, and temporal trends. Join-point regression models were employed to calculate the average annual percentage change (AAPC). Furthermore, age-period-cohort (APC) analyses assessed the effects of age, time, and birth cohort, while an extended autoregressive integrated moving average model (ARIMA model) was used to forecast the psoriasis burden in China from 2022 to 2036.ResultsBetween 1990 and 2021, China experienced significant changes in its age-standardized incidence rate (ASIR), age-standardized prevalence rate (ASPR), and age-standardized DALY Rate (ASDR). Specifically, the ASIR rose from 48 per 100,000 in 1990 to 60 per 100,000 in 2021. Correspondingly, the ASPR increased from 362 per 100,000 in 1990 to 474 per 100,000 in 2021. Finally, the ASDR also showed an upward trend, climbing from 31 per 100,000 in 1990 to 41 per 100,000 in 2021. The AAPC of the ASIR, ASPR, and ASDR in China was 0.7434%, 0.8765%, and 0.8827%, respectively, significantly outpacing the global AAPC of 0.2204%, 0.2220%, and 0.2426%, respectively. The burden of psoriasis in China varied with age and gender, showing a trend of increasing and then decreasing ASIR, ASPR, and ASDR as age advanced. Women experienced lower incidence and prevalence rates of psoriasis than men. Over time, a delay in peak incidence was observed in both genders. The APC analyses revealed that psoriasis incidence initially increased and then declined with advancing age. Across all age groups, earlier birth cohorts had a relatively lower risk. Projections suggest that the incidence and prevalence of psoriasis in China will continue to rise over the next 15 years.ConclusionPsoriasis poses a substantial public health challenge in China due to the country’s large and increasingly aging populace. Mitigating this burden requires a multifaceted approach, including precise epidemiological research, an enhanced understanding of its socioeconomic determinants, and the development of effective health policies.